Pattern and predictors of non-adherence to diabetes self-management recommendations among patients in peripheral district of Bangladesh - Banu, Bilkis; Khan, Md. Mobarak Hossain; Ali, Liaquat; Bärnighausen, Till; Sauerborn, Rainer; Souares-Coutant, Aurélia (Tropical medicine & international health, 2024)
Objectives This study was designed to determine the extent of non-adherence to the different dimensions of diabetes self-management and to identify the factors influencing non-adherence among peripheral patients in Bangladesh. Methods A cross-sectional study was conducted among 990 adult diabetic patients residing in Thakurgaon district, Bangladesh. Data were collected through face-to-face interviews including socio-demographic information, disease and therapeutic, health services, knowledge and adherence to self-management components. Results The proportion of non-adherence to drug prescription was 66.7%, dietary regimen (68.9%), physical exercise (58.0%), follow-up visit/blood glucose test (88.2%), stopping tobacco (50.6%), and regular foot care (93.9%). Significant predictors for non-adherence to drug were poorest socio-economic status (OR = 2.47), absence of diabetic complications (OR = 1.43), using non-clinical therapy (OR = 5.61), and moderate level of knowledge (OR = 1.87). Non-adherence to dietary recommendations was higher for women (OR = 1.72), poorest socio-economic status (OR = 3.17), and poor technical knowledge (OR = 4.68). Non-adherence to physical exercise was lower for women (OR = 0.62), combined family (OR = 0.63), middle socio-economic status (OR = 0.54), and moderate knowledge on physical exercise (OR = 0.55). Non-adherence to follow-up visits/blood glucose test was higher among patients who did not have diabetic complications (OR = 1.81) and with own transport (OR = 2.57), and respondents from high-income group (OR = 0.23) were less likely to be non-adherent. Non-adherence to stopping tobacco was higher for older individuals (OR = 1.86); but lower for women (OR = 0.48), individuals with higher education level (OR = 0.17) and patients sick for a longer time (OR = 0.52). Non-adherence to foot care was higher for patients who needed longer time to go to hospital (OR = 4.07) and had poor basic knowledge on diabetes (OR = 17.80). Conclusion An alarmingly high proportion of diabetic patients did not adhere to diabetes self-management. Major predictors for non-adherence were related to patient's demographic characteristics and their experience with disease, treatment and health care services.